Drying temperature and conditions affect the Origanum dubium Boiss. and Salvia fruticosa Mill. quality attributes and impact the essential oil composition, antimicrobial and antioxidant activities - Chrysargyris, Antonios; Xylia, Panayiota; Tzortzakis, Nikos G. (My University, 2024)
Drying conditions need to be optimized for each medicinal and aromatic plant (MAP) since their composition varies greatly. The present study evaluated the different drying temperatures (20, 35, 42, and 49 °C) and drying conditions (sun, shade, and oven drying) on the quality (chlorophylls and colour indices) of dried Origanum dubium Boiss., Salvia fruticosa Mill. and their essential oil (EO) yield, composition and properties. Both cultivated plants are of industrial interest due to their significant bioactive properties. Results showed that the higher temperature led into faster moisture loss (i.e. 49 °C), and resulted into a darker product (higher browning index). For O. dubium, the proper drying temperature was at 35–42 °C and resulted in producing EO with high antioxidant and antimicrobial activities, due to the increased carvacrol (up to 117 %) and p-cymene (up to 35.4 %) content (oregano EO major compounds). Additionally, O. dubium EO derived from plants dried in an air forced oven (42 °C) revealed greater antimicrobial activity against the four foodborne pathogens investigated compared to sun and shade drying. For S. fruticosa, the optimum drying temperature was at 42–49 °C that produced EOs of significantly higher biological activities (antioxidant and antimicrobial), even though EO yield and main compounds were similar among the investigated temperatures. Shade and oven drying conditions produced EOs with increased biological activities compared to sun drying. Even though drying at 42 °C resulted into a final product of acceptable colour quality indices and EOs with high biological activity, the energy consumption and the calculated carbon dioxide production were the highest. These findings suggest that more traditional methods (i.e. sun and shade drying) can also result into products with appreciated bioactive properties and with a lower environmental carbon footprint, while the drying duration needs to be considered, as valuable factor for industrial applications.
Keywords: Antimicrobial; Antioxidant; Drying process; Energy consumption; Oregano; Sage